Essential role of UCP1 modulating the central effects of thyroid hormones on energy balance - Mayte Alvarez-Crespo; Robert I. Csikasz; Noelia Martínez-Sánchez; Carlos Diéguez; Barbara Cannon; Jan Nedergaard; Miguel López (Elsevier, 2016)
Objective: Classically, metabolic effects of thyroid hormones (THs) have been considered to be peripherally mediated, i.e. different tissues in the body respond directly to thyroid hormones with an increased metabolism. An alternative view is that the metabolic effects are centrally regulated. We have examined here the degree to which prolonged, centrally infused triiodothyronine (T3) could in itself induce total body metabolic effects and the degree to which brown adipose tissue (BAT) thermogenesis was essential for such effects, by examining uncoupling protein 1 (UCP1) KO mice. Methods: Wildtype and UPC1 KO mice were centrally-treated with T3 by using minipumps. Metabolic measurements were analyzed by indirect calorimetry and expression analysis by RT-PCR or western blot. BAT morphology and histology were studied by immunohistochemistry. Results: We found that central T3-treatment led to reduced levels of hypothalamic AMP-activated protein kinase (AMPK) and elevated body temperature (0.7 °C). UCP1 was essential for the T3-induced increased rate of energy expenditure, which was only observable at thermoneutrality and notably only during the active phase, for the increased body weight loss, for the increased hypothalamic levels of neuropeptide Y (NPY) and agouti-related peptide (AgRP) and for the increased food intake induced by central T3-treatment. Prolonged central T3-treatment also led to recruitment of BAT and britening/beiging ("browning") of inguinal white adipose tissue (iWAT). Conclusions: We conclude that UCP1 is essential for mediation of the central effects of thyroid hormones on energy balance, and we suggest that similar UCP1-dependent effects may underlie central energy balance effects of other agents. Keywords: AMPK, Brown adipose tissue, Hypothalamus, Thyroid hormones, UCP1